Desain soal-soal kemampuan literasi matematis untuk siswa SMP - Listri Maya Sari; Adi Asmara (Mahesa Research Center, 2021)
This research aimed to produce questions of mathematical literacy ability of Mathematical literacy ability on Triangular material for Class VII Junior High School students that are valid and practical and have a good level of difficulty and discriminatory index. This research used the Tessmer development model. Tessmer's development stages include preliminary, self-evaluation, expert review, one-to-one, and small group. The test subjects of this study were class VII students of SMP Negeri 02 Kepahiang, totaling 30 students. The selection of test subjects includes high, medium and low abilities. The data analysis technique of this study used qualitative analysis at the expert review and one to one stage and quantitative analysis at the small group stage by analyzing items based on the level of difficulty and discriminating power index. The results of the research show that the 10 questions developed, 10 questions with indicators of mathematical literacy ability on triangular material are valid and practical, 7 questions are said to be good based on the level of difficulty and discriminatory index, so that they can be used by all students of SMPN 02 Kepahiang.